2007
DOI: 10.1007/s10530-007-9146-5
|View full text |Cite
|
Sign up to set email alerts
|

Are there any consistent predictors of invasion success?

Abstract: This article summarises the results of 49 studies that together test the significance of 115 characteristics in 7 biological groups: birds, finfish, insects, mammals, plants, reptiles/amphibians and shellfish. Climate/habitat match, history of invasive success and number of arriving/released individuals are associated with establishment success in at least four independent data sets, both within and across biological groups, and none are contraindicated by other studies. In the introducedinvasive control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
512
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(535 citation statements)
references
References 89 publications
22
512
1
Order By: Relevance
“…Trait-based predictions have had some success in predicting plant establishment, invasiveness and impact (e.g. Pyšek et al 2009; but see Palacio-Lopez and Gianoli 2011), but the distribution of success of such trait comparisons is patchy among animal taxa (Hayes and Barry 2008), with some good predictors of invasion success for birds (Sol et al 2002;Blackburn et al 2009), fishes (Marchetti et al 2004a, b) and mammals , often based on propagule pressure and human affiliation. However, consistent predictors of invasion success across animal and plant taxa remain elusive (Hayes and Barry 2008).…”
Section: Species Traits Comparisons and The Utility Of Functional Resmentioning
confidence: 99%
“…Trait-based predictions have had some success in predicting plant establishment, invasiveness and impact (e.g. Pyšek et al 2009; but see Palacio-Lopez and Gianoli 2011), but the distribution of success of such trait comparisons is patchy among animal taxa (Hayes and Barry 2008), with some good predictors of invasion success for birds (Sol et al 2002;Blackburn et al 2009), fishes (Marchetti et al 2004a, b) and mammals , often based on propagule pressure and human affiliation. However, consistent predictors of invasion success across animal and plant taxa remain elusive (Hayes and Barry 2008).…”
Section: Species Traits Comparisons and The Utility Of Functional Resmentioning
confidence: 99%
“…Domain A: Difficulties arising from society and its relationship to biological invasions, measures that can be taken to overcome them and consequences for the scientific approach of invasion ecology; letters and numbers in parentheses refer to Perrings et al (2010b); c Bremner and Park (2007), Burt et al (2007), Byron (2008); d Mack et al (2000), Moore et al (2010); e Fischer and van der Wal (2007); f Andreu et al (2009); g Bodey et al (2010) to analyze, explain, and predict. Invasion processes are complex (Lodge 1993;Hayes and Barry 2008;B1 in Table 2) and context-dependent (Zedler and Kercher 2004;Gurevitch et al 2008;Blackburn et al 2009) (B2 in Table 2). This creates the need for methods that are able to explain and predict multiple interacting influences (Heger and Trepl 2003), and to take into account the history of current invasions for their explanation (Cassey et al 2005) (see right column in Table 2).…”
Section: Domain B: Difficulties Arising From the Peculiarity Of The Imentioning
confidence: 99%
“…Thus, the reason for this order of occupation of non-native areas is the landscape similarity between native areas in Africa and non-native areas found in southern Brazil. Hayes and Barry (2008) showed that climate/habitat match and number of introduced organisms are consistently significant predictors of successful establishment across all of the biological groups in which they have been tested (birds, mammals and plants). The initial occupation of the state of Rio Grande do Sul (southern Brazil) is justified by the similarity between this region and the native African range of the cattle egret.…”
Section: Discussionmentioning
confidence: 99%
“…This dispersion pattern is not expected for the cattle egret in Brazil due to the lack of uniformity in the landscape. During colonization, the habitat match is an important factor to consider because it can determine the selection of areas to be occupied by invasive species (Hayes and Barry 2008). The state of Rio Grande do Sul in southern Brazil is the only region of the country with extensive areas of natural grasslands within the "Pampas" biome (taken from MMA) and had the largest bovine breeding activities in the 1970s (census data;IBGE 1975), which are similar to conditions found for the cattle egret in its native range.…”
Section: Introductionmentioning
confidence: 99%